(untitled) (Archive of Conferences, 2021)
Hygiene is usually related to the causes of the disease and their elimination. In a sense, it falls into the realm of preventive medicine. When we talk about food hygiene, we mean all the work done to create a favorable environment for the consumer table at different stages of production to produce healthy food. It is in this article that a study has been conducted on the storage of each food and their proper storage